Concept of "AMA DOSHA"Â WSR to free radicals - Kumar, Munish; Kumar, Parvesh (Journal of Applied Pharmaceutical Research, 2016)
Ama is considered as root cause of all diseases in the body. It has tremendous capacity to vitiate the Doshas and disturbing the homeostasis (Dhatusamya).Ã  Ama is the result of improper digestion or partially digestion of the food particle due to hypo function of Jatharagni and also due to accumulation of mala in the body. In modern physiology, Ama can be correlated with deadly Free radicals. Free radicals are atoms, ions or molecules that contain one or more unpaired electron, which requires neutralization by free radical scavengers. The majority of free radicals that damage biological systems are oxygen free radicals, and these are known as Ã¢â¬ÅReactive oxygen speciesÃ¢â¬Â. Thus it exists in incomplete metabolic state which is also the state of Ama described as Avipakam (incompletely metabolized).Ã  This Ama is responsible for the production of various diseases. In the same way, free radicals are also found to be root cause of many diseases. The aim of present article is to understand the concept of Ama as well as free radicals as a root cause of diseases and its treatment.